Nutritional knowledge among coaches and personal trainers in Kuwait: a cross sectional study - Almansour, Fawaz D; Allafi, Ahmad R; Aldughpassi, Ahmed; Al-Haifi, Ahmad R (Progress in Nutrition, 2020)
Personal Trainers (PT’s) or Coaches are becoming the new trend in Kuwait and taking the role ofdietitians and nutritionists in terms of providing nutritional advice. No research has been done in the past togauge the knowledge of coaches and trainers in Kuwait. The aim of this cross-sectional study was to examinethe nutrition knowledge among coaches and PT’s for both genders within all groups. Data were collected fromindependent personal trainers and coaches across different gyms from different areas in Kuwait. The 100 participants consisted of males (n=50) and females (n=50) engaged in different types of sports. Participants answered questions testing their nutritional knowledge and scientific background. Adequate nutrition knowledge was defined as an overall score of 75% in all domains (highest achievable score was 100%). Participants averaged 56% in all domains. Male participants averaged 55% and female participants averaged 56.8%. Overall, we demonstrated that personal trainers and coaches have inadequate nutrition knowledge. When comparing genders, female participants had slightly more nutrition knowledge than male participants. Therefore, proper nutrition education is integral for both male and female personal trainers. Proper nutrition courses and workshops should be provided for coaches and personal trainers in order to improve their nutrition knowledge, as it is important to help them provide adequate nutrition advice for their clients. Moreover, follow-up exams or certifications are recommended every two years to ensure that personal trainers and coaches’ nutrition knowledge are maintained and up to date.